Ultra wideband systems technologies and applications - Ajello, R. (Roberto); Batra, Anuj. (Boston, Mass. ; London : Newnes, 2006)
Ultra wideband technology turns the radio spectrum available to wireless applications from a country road into a high-speed ten lane super freeway, and the destination is the future of wireless technology. UWB is a huge leap forward because it offers wide bandwidth with little interference, allowing multiple UWB signals to share a single channel. This multi-author volume, compiled under the guidance of Dr. Roberto Aiello, introduces the theory and concepts behind ultra wideband (UWB) systems as well as their applications. Authors include those involved in creating the UWB standards, researchers, and applications specialists. This book has been broken down into three parts: introduction to UWB, different techniques available, and applications. Within these sections topics covered are UWB spectrum and regulations, UWB channels, modulation techniques, antennas, signal propagation, and UWB transceiver architectures. This book has all the information RF/wireless engineers will need to understand this burgeoning technology. *An all-star list of contributors covers the subject more authoritatively than any single author could *Discusses U.S. and international ultra wideband regulations *Includes material on antenna systems and signal propagation at ultra wideband frequencies.
History of ultra wideband communication systems -- UWB spectrum and regulations -- Interference and coexistence -- UWB antennas -- Direct-sequence UWB -- Multiband approach to UWB -- Spectral keying : a novel modulation scheme for UWB systems -- Multiband OFDM -- MAC designs for UWB Systems -- Standards for UWB communications -- Commercial applications.
Includes bibliographical references and index.
Keywords: Broadband communication systems; Ultra-wideband devices; Wireless communication systems; Electronic books